Reducing nihilism in metastatic pancreatic ductal adenocarcinoma: Treatment, sequencing, and effects on survival outcomes - O'Reilly, Eileen M. (Cancer Med, 2020)
BACKGROUND: Real‐world practice patterns, treatment sequencing, and outcomes in patients with metastatic pancreatic cancer remain unclear. Previous research indicates that the likelihood of patients with metastatic pancreatic cancer receiving or continuing cancer‐directed therapy is low—a phenomenon called nihilism. This retrospective, descriptive analysis examined clinical characteristics, treatment patterns, and outcomes for patients with metastatic pancreatic ductal adenocarcinoma (mPDAC). METHODS: Treatment patterns were examined using electronic health records from the Flatiron Health database covering the period from January 1, 2014, to June 30, 2019. Real‐world overall survival [rwOS]) was compared for a subgroup of patients receiving treatment and a matched subgroup not receiving treatment. RESULTS: Of 7666 patients, 5687 (74.2%) received at least one line of systemic therapy. A greater proportion of patients receiving treatment than not receiving treatment had an initial diagnosis of stage IV disease (68.8% vs 61.2%, respectively). Among patients receiving an initial therapy, fewer than half (38.2%; 2174/5687) received second‐line treatment, mostly because they died, and only 34.3% (745/2174) of those receiving second‐line treatment advanced to third‐line treatment. The rwOS for patients receiving at least one line of systemic therapy was 8.1 months versus 2.6 months for matched patients not receiving treatment (hazard ratio, 0.41; 95% confidence interval, 0.38‐0.45; 1470 patients per group). CONCLUSIONS: Systemic therapy provided significant clinical benefit for patients who were eligible and chose to receive it, particularly when treatment was consistent with guideline recommendations. The large proportion of patients initiating treatment suggests that nihilism with mPDAC is diminishing.